Scaffolding Technique in Reading Comprehension in The Junior High School - Narina, Luh Rita (English Education Department STKIP Agama Hindu Singaraja, 2022)
The general objective of this research is to describe and analyze the steps in implementing scaffolding technique in reading comprehension and the students reading comprehension implemented through the scaffolding technique in seventh grade student in SMP Negeri 4 Busungbiu in the 2021/2022 academic year. This research is classroom action research. The research subjects were 31 seventh grade students. The researcher used two methods, namely quantitative (student ability in reading comprehension) and qualitative data (data on the implementation of reading comprehension sessions through scaffolding technique and the teachers’ difficulties in implementing reading comprehension sessions through scaffolding technique). The results show that: (1) Scaffolding teaching techniques can improve students' reading comprehension in descriptive and procedure texts, namely: ((a) finding general themes b) finding specific information contained in the text, 3) being able to know the appropriate pronouns in the text (d) students being able to understand the meaning of words in the text. Scaffolding teaching techniques can improve classroom situations, in terms of (a) increasing student participation; (b) creating a more interesting teaching atmosphere (c) increasing students' attention to the lesson; (d) increasing the class of cooperation. From the results of this study, it can be concluded that this technique of scaffolding teaching is effectively used to improve students' reading comprehension.